2014
DOI: 10.1111/ecc.12185
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life during chemotherapy and satisfaction with nursing care in Turkish breast cancer patients

Abstract: This descriptive cross-sectional study aimed to evaluate quality of life for breast cancer patients (n = 105) undergoing chemotherapy, and to assess their satisfaction with nursing care. It also explored relationships between quality of life, satisfaction with nursing care, and demographic and disease-related characteristics. Ethics approval for this study was provided. The research was carried out between October 2011 and June 2012. Quality of life and satisfaction with nursing care were assessed using the Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
3
21
0
3
Order By: Relevance
“…(19) In contrast, Hoyer et al (12) observed scores greater than 80% in physical functioning among Swedish women on chemotherapy, and mean values above 75% also for social functioning, indicating no impairment of QoL in relation to these functions. Analogous results were found in a similar study conducted in Malaysia, with mean values above 75% for physical and social functioning, which positively characterizes the maintenance of living conditions, and social and leisure activities among affected women.…”
Section: Discussionmentioning
confidence: 93%
“…(19) In contrast, Hoyer et al (12) observed scores greater than 80% in physical functioning among Swedish women on chemotherapy, and mean values above 75% also for social functioning, indicating no impairment of QoL in relation to these functions. Analogous results were found in a similar study conducted in Malaysia, with mean values above 75% for physical and social functioning, which positively characterizes the maintenance of living conditions, and social and leisure activities among affected women.…”
Section: Discussionmentioning
confidence: 93%
“…Understanding the impact of breast cancer treatment on the QoL of patients is not only important for patients and their health care providers but also critical for policymakers to evaluate the cost‐effectiveness of cancer treatments. Most previous studies focused on the QoL associated with a specific breast cancer treatment of interest (i.e., tamoxifen only; Boehm et al, ; Kilickap et al, ; van Nes et al, , AIs only; Kilickap et al, ; Laroche et al, ; van Nes et al, , chemotherapy only; Bayram et al, ; Browall et al, ; Galalae et al, ; Ganz et al, ; Hwang et al, ; Tiezzi et al, , radiotherapy only; Rahn et al, ; Xiao et al, , mastectomy only; Kaminska et al, ; Szutowicz‐Wydra et al, ), whereas this study comprehensively evaluated the QoL across different cancer treatments. We found that the use of chemotherapy had the most significant association with the QoL of breast cancer survivors, with adjustment for patient's characteristics and other breast cancer treatments; no significant association was not found for other types of breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the majority of studies on the QoL of breast cancer patients were conducted in Western countries (Cerezo et al, 2012;Conde et al, 2005;Ganz et al, 2002Ganz et al, , 1990Huguet et al, 2009;Joly et al, 2000;Kontodimopoulos, Ntinoulis, & Niakas, 2011;Shimozuma et al, 1999), and thus the results may not be relevant or directly applicable to Chinese patients living with cancers, who have distinct social and cultural differences, and unmet needs (Fang, Cheng, & Lin, 2018) from Western societies. There is also a lack of comparative results between the QoL associated with different breast cancer treatments, as most previous studies focused on a single form of therapy (e.g., chemotherapy only; Bayram, Durna, & Akin, 2014;Browall et al, 2008;Galalae et al, 2005;Ganz et al, 2002;Hwang et al, 2013;Tiezzi et al, 2017). Therefore, the aims of the present study were to evaluate the associations of different cancer treatments with the QoL of Chinese breast cancer survivors in Taiwan, specifically for the HR-positive/HER2-negative subtype.…”
mentioning
confidence: 99%
“…Two case-control studies and one longitudinal study were of high quality (six stars out of nine). Ahmed et al [21] Cross-sectional ** ** * 5(/6) Ahrafizadeh et al [22] Cross-sectional ** * 3(/6) Akel et al [23] Cross-sectional ** * 3(/6) Akin et al [24] longitudinal *** ** 5(/9) Alawadi et al [25] Cross-sectional ** ** * 5(/6) Albabtain et al [26] Cross-sectional ** * 3(/6) Almutairi et al [27] Cross-sectional ** ** * 5(/6) Al Naggar et al [28] Cross-sectional ** ** * 5(/6) Al Natour et al [29] Cross-sectional ** * 3(/6) Bayram et al [31] Cross-sectional ** * 3(/6) Filazoglu et al [32] Cross-sectional ** ** * 5(/6) Hujeir et al [33] Cross-sectional ** * 3(/6) Jafari et al [34] Cross-sectional ** * * 4(/6) Jassim et al [35] Cross-sectional ** ** * 5(/6) Khalili et al [36] Cross-sectional ** * 3(/6) Kiadaliri et al [37] longitudinal *** ** 5(/9) Mohammadi et al [38] Cross-sectional ** * 3(/6)…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Several socio-demographic factors were closely associated with HRQoL in patients with BC. These included: age [21,24,41,43,45,49], marital status [24,37], level of education [22,31,40,44,51], employment status [47,48,51], income [22][23][24][25]28,39,48], and having children [37]. Regarding age, the direction of the association was not consistent across studies, with three studies reporting a negative association with HRQoL [21,24,49], while three other studies reported the opposite [41,43,45].…”
Section: Socio-demographic Factorsmentioning
confidence: 99%